Does Brazil have a Legislative Policy?. (1st September 2016) - de Paula, Felipe
ABSTRACT: This article debates Brazilian legislative policy, accepted as a meta policy focused on normative quality and performance, both on formal and substantive aspects. The main object is to show that, despite the fact that the country has a formal policy at least since 2002, there is a wide gap between normative requirements and lawmaking practice. Both recent literature and the perception of high level governmental actors do converge in this direction. One of the central elements of the Brazilian legislative policy – Decree 4, 176/2002 – is widely seen as a fictional tool. To confirm this statement, I first bring a short background about institutions and legislative process in Brazil, focusing on some particularities as the crucial role of the Executive branch in the lawmaking process. I then debate the theory and practice of Brazilian lawmaking and rulemaking, with special emphasis on the legislative policy stated by Decree 4, 176/2002. The realist dichotomy, law in books and law in action, will be a theoretical guide here. Then, I discuss the technical aspects that (were expected to) surround the legislative production, particularly the substantive ones. The opinion of important high-level governmental actors that have dealt with drafting and regulation in the last ten years, captured by a semi-structured survey, is then shown. They confirm the idea that Brazilian legislative meta policy has a low impact on the legal elaboration, and is not seen as convenient to the contemporary governmental actions. But they also say there is large room for improvement.